Le conflit du Honduras et du Salvador de 1969 - Holly, Daniel (Études internationales, 1979)
When on July 16th war broke out between Honduras and El Salvador, their comparative strengths were such that El Salvador quickly assumed the upper hand. Its troops routed the adversary and occupied large sections of Honduran territory. The advantage gained by El Salvador from its victory was of short duration however. The intervention of the OAS forced an end to the hostilities and obtained from El Salvador the evacuation of the conquered geographical space. This war nevertheless constituted only a moment of a conflict that has already lasted a very long time. Migratory questions are at the heart of the outstanding differences between the two countries. El Salvador refused to accept that its national domiciled in Honduras should have heir possessions seized and be returned to their country of origin while Honduras, alarmed and fearing the consequences of a clandestine occupation of its territory, intended to put an end to that situation. The two adversaries' determination was such that negotiations and bargaining were powerless to bring their positions closer together. Confronted with this impasse, the Honduran authorities decided to proceed unilaterally and war ensued. The calculation was not unfounded since El Salvador did not succeed in gaining the fruits of its victory. Its objectives — protection of human resources and systemic relations — were far from achieved. It was therefore Honduras that appeared to be in a better position. The expulsion and dispossession of Salvadoran nationals continued after the cessation of hostilities. The hoped for restructuration of systemic relations between the two countries is progressing despite the threats and protests of the Salvadoran government.